2020
DOI: 10.1093/jas/skaa002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding barley or corn silage with dry-rolled barley, corn, or a blend of barley and corn grain on rumen fermentation, total tract digestibility, and nitrogen balance for finishing beef heifers

Abstract: Five ruminally cannulated heifers were used in an incomplete 6 × 6 Latin square design to determine the effects of cereal silage (barley vs. corn), cereal grain (barley vs. corn vs. a 50:50 blend of barley and corn), and their interaction (S × G) on dry matter intake, ruminal fermentation, total tract digestibility, nitrogen balance, and in situ degradation. Corn silage (CS) or barley silage (BS) was included at 8% of dietary dry matter (DM). Within each silage source, diets contained (DM basis) either dry-rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The reason for elevated n-6 fatty acids when feeding the blend are not related to the dietary supply, but instead likely relate to effects on rumen pH. Lower rumen pH was found in blended compared with barley and corn grain-fed steers in the present study, as previously reported by Johnson et al [ 41 ]. Under these conditions, lipolysis of dietary lipids could have been inhibited [ 42 ], reducing PUFA biohydrogenation by rumen bacteria, and allowing for greater bypass of n-6 fatty acids.…”
Section: Resultssupporting
confidence: 86%
“…The reason for elevated n-6 fatty acids when feeding the blend are not related to the dietary supply, but instead likely relate to effects on rumen pH. Lower rumen pH was found in blended compared with barley and corn grain-fed steers in the present study, as previously reported by Johnson et al [ 41 ]. Under these conditions, lipolysis of dietary lipids could have been inhibited [ 42 ], reducing PUFA biohydrogenation by rumen bacteria, and allowing for greater bypass of n-6 fatty acids.…”
Section: Resultssupporting
confidence: 86%
“…The reason for decreased starch digestibility in BS-100 could be the sharply reduced ruminal pH, resulting in subacute rumen acidosis in the lambs, which thereby limited starch degradation in rumen and intestine ( 28 , 29 ). However, several studies indicated that increasing dietary barely grain improved the total tract starch digestibility because of its high rumen degradation rate ( 5 , 30 ). The inconsistent results among studies were likely due to differences in diet treatments, dietary starch contents, and experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results among studies were likely due to differences in diet treatments, dietary starch contents, and experimental animals. For example, Johnson et al ( 5 ) reported a greater starch digestibility for barley-based diet than that for corn-based diet at a dietary starch content (ranged from 55.4 to 62.25%) was reported in beef cattle. The current results indicated that partially substitute CS with BS could decrease total tract fiber digestibility for fattening sheep, and total substitute CS with BS would decrease both fiber and starch digestibility for fattening sheep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations